Protecting the infrastructure: 3rd Australian information warfare & security conference 2002 - Hutchinson (Ed.), William (2002)
The conference is hosted by the We-B Centre (working with a-business) in the School of Management Information System, the School of Computer & Information Sciences at Edith Cowan University. This year's conference is being held at the Sheraton Perth Hotel in Adelaide Terrace, Perth. Papers for this conference have been written by a wide range of academics and industry specialists. We have attracted participation from both national and international authors and organisations. The papers cover many topics, all within the field of information warfare and its applications, now and into the future. The papers have been grouped into six streams: • Networks • IWAR Strategy • Security • Risk Management • Social/Education • Infrastructur